Design and Implementation of Odoo ERP Application as a Solution to Re-quirement of ULVA-Q MSME Business Information Systems Pangandaran - *Nurul Mardhiah; Ginulur Rahayu; Dwi Oktavia (Universitas Syiah Kuala, 2022)
ULVA-Q is an MSME engaged in the food beverage industry that sells products the form of seaweed. The purpose of this research is to find out what information systems are needed by ULVA-Q SMEs. The method used in this study is a qualitative method with data collection in the form of primary and secondary. Primary data was obtained through the interview process, while secondary data was obtained through information on similar existing research or literature studies and conducted previously so that we can compare it with the research we have just done. The result of this research is the implementation of the Odoo application on ULVA-Q by using the website and social marketing modules.